"Fundamentally Flawed?". Issue 2 (17th July 2014) - Kaiser, Kimberly A.; Spohn, Cassia
<x xml:space="preserve">Abstract</x> Research Summary Using U.S. Sentencing Commission data, this study assesses whether judicial downward departures are more prevalent among child pornography offenders compared with a matched sample of defendants convicted of other offenses. Additionally, we examine reasons given by judges when departing from the guidelines for these offenders. We found that child pornography defendants received significant reductions in sentences by way of judicial downward departures. Policy Implications In 2007, the Supreme Court considerably altered the federal sentencing process. In Kimbrough v. United States (2007), the Court held that judicial departures were permissible on grounds of a policy disagreement. Many circuit courts have authorized sentencing judges to depart from the guidelines in child pornography cases based on such a policy disagreement. The findings of this study suggest that judicial downward departures for these offenders cannot be explained by individual characteristics, such as race, gender, or age, and may be indicative of a specific disagreement with this particular sentencing policy. An examination of the reasons provided by judges supports the hypothesis that judges may be attempting to remedy what they perceive as unjustly harsh sentencing guidelines.